Breakfast consumption patterns and associated factors among adolescent high-school students in Tullo District, Eastern Ethiopia - Natnael Teferi; Tara Wilfong; Dawit Firdisa; Samrawit Berihun; Behailu Hawulte (PLoS ONE, 2025)
Background There is growing proof to recommend eating breakfast has positive health and school-related outcomes for adolescents, including improved performance, attention, brain development, and physical growth. However, there is a dearth of evidence on the comprehensive understanding of breakfast consumption patterns and associated factors. Therefore, this study aimed to assess breakfast consumption patterns and their associated factors among adolescent high school students in the Tullo district, Eastern Ethiopia. Methods An institution-based cross-sectional study design was conducted among 405 randomly selected adolescent high school students in the Tullo District, Eastern Ethiopia, from October 09–29, 2023. A self-administered questionnaire was utilized to collect the data. Epidata version 4.6 and SPSS Statistics version 27.0.1 were used for data entry and analysis, respectively. Both bivariable and multivariable logistic regression analyses were performed to identify the factors associated with breakfast consumption patterns. An adjusted odds ratio (AOR) with a 95% confidence interval (CI) was calculated to determine the strength of the association, and a p-value of 0.05 was used to determine statistical significance. Result Nearly half, 46.2% (95% CI: 41.5, 51.4), of participants had irregular breakfast consumption (skipped). Being female (AOR = 5.28; 95% CI: 2.69, 10.36), family size of >5 (AOR = 4.76; 95% CI: 2.41, 9.36), being a rural resident (AOR = 3.34; 95% CI: 1.78, 6.25), no formal maternal education (AOR = 3.89; 95% CI: 2.09, 7.22), chewing khat (AOR = 3.13; 95% CI: 1.59, 6.16), cigarette smoking (AOR = 3.06; 95% CI: 1.02, 9.17), and eating disorders (AOR = 6.54; 95% CI: 2.19, 19.43) were significantly associated with irregular breakfast consumption patterns among adolescents. Conclusion The findings of this study showed that the prevalence of irregular breakfast consumption (breakfast skipping) among adolescent high school students was high. Being female, rural residency, no formal maternal education, current smoking of cigarettes, current khat chewing, and eating disorders were identified as factors associated with breakfast consumption patterns. Given that almost half of adolescents in Tullo District skip breakfast, several modifiable factors associated with this practice, focused interventions are essential.